Avoiding SARS-CoV-2 infection in healthcare workers: is behavioral change the answer? - Morales-Burton, Verónica; Lopez-Ramirez, Sofía A. (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic has become an important cause of morbimortality, and healthcare workers are at the highest risk of infection. As a result, policies and guidelines have been issued, and behavioral changes have been crucial in hospitals. Among these measures, the implementation of personal protective equipment (PPE) and its appropriate use in the workplace is key to avoiding contagion, as is understanding new measures regarding patient admission, distribution, constant education on virtual platforms, among others, and changing conduct to reduce contagion. However, behavioral change interventions in healthcare workers are challenging as contextual characteristics, attributes of the intervention, and psychological factors are involved. Study objectives The issue under investigation is the impact of COVID-19 on frontline healthcare workers in the emergency department of the Fundación Cardioinfantil (FCI). The objective was to describe their behavioral changes by studying and monitoring SARS-CoV-2 infection and their relationship through the tracing process in 2020. Methods We conducted a case study to identify and relate the SARS-CoV-2 infection rate within the personnel in the department and the response of healthcare workers to the implementation and adherence to the use of PPE through the analysis of the different variables that contributed to behavioral change. Data were collected by a single author and analyzed by two authors using both the individual-level logic model technique and the triangulation of information, with approval from the institutional review board. Discussion Several interventions for behavior change were registered in the data collection process. The data obtained indicated that implementation, embedding, and integration were perceived as collective and individual behavioral processes. This was supported by evidence from healthcare interventions, such as education, incentivization, training, restriction, environmental restructuring, modeling, and enablement. Conclusion Behavioral science should be part of public health responses, as the theoretical basis suggests that change may modify the response to avoid the transmission of infectious diseases. Therefore, individuals at the highest risk appear to adopt guidance with targeted behavior adaptation interventions. Efforts to inform, instruct, and motivate healthcare workers must be continuous, and actions at the community level must be strengthened, as it is human behavior that determines the spread and mortality of infectious diseases, where community compliance to preventive behaviors plays a crucial role.